Spiritual Culture: Its State and Its Problems - Černienė, Bronė (Problemos, 1988)
In the article the concepts of “spiritual culture” and “spiritual life” are discussed and the state of the Soviet spiritual culture is diagnosed. A particular attention is paid to some disparity existing between the levels of the material culture and the spiritual culture, as well as to the topical dilemma of moral life and the humanistic potential of the personality. The author of the article maintains that the harmonious development of both cultures in the socialist society can be achieved via the humanisation of education and science as well as by active improvement of all essential powers of man and social spiritual life.